ECOLOGICAL HAZARD ASSESSMENT OF THE ATMOSPHERIC AIR AT THE URBAN ECOSYSTEM BY THE STATE OF THE DEPOSIT ENVIRONMENT - Barabash, Olena (Proceedings of National Aviation University, 2019)
Industrial activity and emissions of road transport is one of the major sources of pollution in urban ecosystems and poses a significant threat to the health of urban populations due to dust emissions into the atmosphere. The high cumulative capacity of toxic metals, in particular the plumbum, leads to its entry into the atmospheric air, soil and groundwater, and ultimately to accumulation in the tissues and organs of plant organisms. There is a correlation between the content of toxic metals in the atmospheric air and their fallout within the sanitary protection zone of industrial and motor transport enterprises and distribution throughout the urban ecosystem. Snow cover stores pollution, thus, it is often used to assess the state of the air. The layer-by-layer sampling of the snow cover allows determining the pollution dynamics and the influence of the production capacities of enterprises on the state of the urban ecosystem. The bioassay methods using plant organisms as test objects is based on their sensitivity to exogenous chemical effects and is reflected in the response of plants to pollutants. Determination of physico-chemical parameters of the snow cover and calculation of phytotoxic effect based on the phytotesting methods allows to detect not only the presence of toxic metals in the snow cover, but also to obtain reliable information about their distribution in the atmospheric air of cities. According to the researches results, the indexes for the lengths of Lepidium sativum shoots were obtained. The test object was germinated in a snow cover sampled at a distance of 5 to 50 m near the WOG filling station enterprise. The data obtained were compared with the values of the shoots length of test objects germinated in snow samples from the territory of the park area. It was established that the level of atmospheric air pollution with toxic metals is the highest at a distance of 50 m from WOG filling station. The physico-chemical parameters of the snow cover and the phytotoxic effect indicate a high probability of toxic metals entry into the atmospheric air beyond the limits of the sanitary protection zone of WOG filling station and into the residential areas.